In der Welt träumen (englisch) - Philippson, Peter (Psychotherapie-Wissenschaft, 2021)
I think dreams are very important in a number of ways. I share a sense of the significance of dreaming with Sigmund Freud and Fritz Perls. I regularly bring work with dreams into my therapy, training and groupwork as a way that orients our sense of what is happening both individually and collectively. I will write this in two parts. The first part is an overview of how I understand dreams and different ways I have been working with them as a therapist. The second part introduces a way of working with dreams that I have developed in the past few years, that takes both the understanding and the work in a different direction that collapses the strict separation between waking and dreaming.